The role of psychology in teaching foreign languages - Ruzmetova Zilolakhon Dilmuradovna (Zien Journals, 2024)
In this article, the influence on the successful learning of a foreign language factors are discussed and it demonstrates the relation between progress in studying foreign language and effective using the psychology. The author talks about interdependence and the process of learning a foreign language. Methodological and psychological aspects of learning a foreign language are presented.
Keywords: psychology; foreign languages; the role of a teacher; teaching methodology